Demographic Determinants of Fire-Safety Behavior in High-Rise Residential Buildings: A Survey-Based Behavioral Analysis from Bengaluru, India - N., Mamatha; CK., Ajai Chandran (Engineering, Technology & Applied Science Research, 2026)
This study explores the role of demographic and experience-based parameters for fire safety behavior among residents of high-rise residential apartment buildings in the city of Bengaluru, a metropolitan capital in India. Data were gathered through a questionnaire-based survey among 262 residents. Multiple regression analysis was used to assess the correlation among demographic parameters and behavioral responses during evacuation. The results show that age (R² = 0.154, p = 0.004), presence of vulnerable household members (R² = 0.137, p = 0.022), and prior fire experience (R² = 0.157, p = 0.004) are statistically significant predictors of fire-safety behavior. In contrast, gender (R² = 0.117, p = 0.073), educational qualifications (R² = 0.109, p = 0.136), and chronic health conditions (R² = 0.121, p = 0.500) do not exhibit significant associations. Cross-tabulation analysis further indicates that residents who have received fire-safety training prioritize immediate evacuation, whereas untrained residents display delay behaviors. By providing empirical behavioral evidence from an Indian metropolitan context, this study highlights the demographic heterogeneity in evacuation behavior and supports the integration of behavioral realism into performance-based fire safety design for high-rise residential buildings.